A solvent-free synthesis of coumarins using a Wells-Dawson heteropolyacid as catalyst - Romanelli, Gustavo Pablo (2004)
Substituted coumarins are synthesized from phenols and b-ketoesters by the Pechmann reaction, using a Wells–Dawson heteropolyacid (H6P2W18O62Æ24H2O) as catalyst by a solvent-free procedure. This one requires low reaction times, 130°C temperature and as little as 1mol% of Wells–Dawson acid, obtaining good to excellent yields of coumarins. The catalyst showed to be reusable with no differences in the yields. The results are compared with those of the reactions performed in toluene solution. The presented synthetic procedure is a convenient, clean and fast alternative for synthesizing 4-substituted coumarins (17 examples).